2018
DOI: 10.1152/ajpheart.00725.2017
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic conditioning in blood vessels and smooth muscle tissues: effects on function, mechanisms, and unknowns

Abstract: Hypoxic preconditioning, the protective effect of brief, intermittent hypoxic or ischemic episodes on subsequent more severe hypoxic episodes, has been known for 30 yr from studies on cardiac muscle. The concept of hypoxic preconditioning has expanded; excitingly, organs beyond the heart, including the brain, liver, and kidney, also benefit. Preconditioning of vascular and visceral smooth muscles has received less attention despite their obvious importance to health. In addition, there has been no attempt to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 199 publications
(195 reference statements)
0
6
0
1
Order By: Relevance
“…Hypoxic (pre)conditioning is characterized by repeated exposures to hypoxia at sub‐harmful levels aiming to induce adaptations that render cells and tissues less vulnerable to subsequent hypoxic insults (Noble, 1943). Crucial regulators of these adaptations are the hypoxia‐inducible factors (HIFs) (Almohanna & Wray, 2018) that can activate a large number of molecular effectors including EPO (Ruscher et al., 2002) and vascular endothelial growth factor (VEGF) (Sondell et al., 1999). The main protective molecular adaptations achieved by hypoxic conditioning are believed to comprise improved vascularization, antioxidant capacities, and bioenergetics.…”
Section: Might Exposure To Altitude/hypoxia Provide Benefits Through mentioning
confidence: 99%
“…Hypoxic (pre)conditioning is characterized by repeated exposures to hypoxia at sub‐harmful levels aiming to induce adaptations that render cells and tissues less vulnerable to subsequent hypoxic insults (Noble, 1943). Crucial regulators of these adaptations are the hypoxia‐inducible factors (HIFs) (Almohanna & Wray, 2018) that can activate a large number of molecular effectors including EPO (Ruscher et al., 2002) and vascular endothelial growth factor (VEGF) (Sondell et al., 1999). The main protective molecular adaptations achieved by hypoxic conditioning are believed to comprise improved vascularization, antioxidant capacities, and bioenergetics.…”
Section: Might Exposure To Altitude/hypoxia Provide Benefits Through mentioning
confidence: 99%
“…The bark dents on the surface of arterioles are made by the smooth muscle fibres of the vascular endothelium (X. Xu, Xu, et al., 2019 ). Vascular smooth muscle cells, which generally have a tapered shape, play an important role in regulating the rate of blood flow and maintaining vascular tension, and increased blood flow velocity leads to an increase in oxygen supply to tissues (Almohanna & Wray, 2018 ; Padget et al., 2019 ). Some studies found constriction of smooth muscle cells on the surfaces of arterioles in the lungs and the ventricular wall in yaks (He, 2007 ; Zhou et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…110 Several systemic, brain-specific and cellular physiological adaptations are implemented to mitigate the detrimental consequences of hypoxia on the brain. [111][112][113][114][115][116][117][118][119] As described above, peripheral chemoreceptor-induced hyperventilation 120 and cardiac output 121,122 enhance systemic and brain oxygenation. Metabolic autoregulation and neurovascular coupling 95,123 acutely modulate the cerebral blood flow in response to hypoxia.…”
Section: Relation Between Cardiovascular Pathologies and Neurodegenerative Diseases At Altitudementioning
confidence: 91%
“…126,127 At the cellular level, responses to hypoxia are mediated by numerous biochemical adaptations 111 protection of mitochondria, 115 boosting of antioxidant defense mechanisms 113,116 and attenuation of cell death. 117 These effects of hypoxia exposure suggest its potential application to counteract age-related and pathological alterations of cerebral blood flow and cerebrovascular alterations. The role of aging-related cerebrovascular deterioration and cerebral blood flow dysregulation on cognitive dysfunction has been reviewed by Toth et al 95 and pathological alterations in neurovascular function are proposed to be key mechanisms in the pathogenesis of Alzheimer's disease.…”
Section: Relation Between Cardiovascular Pathologies and Neurodegenerative Diseases At Altitudementioning
confidence: 99%